Pengaruh Cendawan Mikoriza Arbuskula Terhadap Pertumbuhan Bibit Pepaya (Carica papaya L.) Kultivar Caliana - Amran Jaenudin; Yora Erviani; Siti Wahyuni (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2015)
The objective of this research is to know the effect of Vesicular Arbuscular Mycorrhizae (VAM) on the growth of papaya (Carica papaya L.) cv Calina seedling. The experiment was conducted in the village of the District Wanayasa Beber Cirebon. The location is 250 m above sea level, Latosol field, the type of rain including rain type C (rather wet). The time of research was conducted on May to June 2014. The research method used the experimental method with randomized block design (RBD). This experiment consists of 6 (six) treatment and repeated 4 (four) times. Variables observed that plant height, stem diameter, leaf length, number of leaves crop, fresh weight, and root volume. The research showed that treatment of Vesicular Arbuscular Mycorrhizae (VAM) did not significant effect on growth variables papaya seedling. The treatment of 15 g and 20 g VAM/ plant given a good effect on the root volume.